Microfacies, diagenesis and hydrocarbon potential of Eocene carbonate strata in Pakistan - Khitab, U. (Springer, 2020)
The role of microfacies and diagenesis was focused to assess the hydrocarbon potential of Eocene carbonate strata exposed in SulaimanâHazara mountain ranges. Thin- to thick-bedded Eocene limestone exhibits wackestone, packstone, mudstone, and grainstone texture and comprises larger benthic forams such as Nummulite, Assilina, Lockhartia, Discocyclina, Orbitolites and Operculina. The accumulation of the strata occurred in lagoon, inner to deeper shelf. The microfacies and textural variations revealed stable shallow shelf conditions in early Eocene. The marine sedimentation ceased in Hazara and Salt ranges, but Kohat and Sulaiman regions remained under water during middle Eocene. The deposition of Habib Rahi Formation in deeper shelf attests to local scale normal faulting due to the northward movement of the Indian Plate. The Eocene reservoir zones were sourced by Patala and Ghazij Formations and capped by thick cover of fluvial shale, establishing favourable conditions for stratigraphic traps. Thick limestone packages of foraminiferal wackestone/packstone and dolomitized/dolomitic wackestone microfacies are regarded as estimable targets for hydrocarbons exploration in the region. Several diagenetic processes were observed in the studied limestone which includes: micritization, dolomitization, neomorphism, cementation, mechanical and chemical compaction, fracturing and dissolution which were caused in marine, meteoric and burial diagenetic environments. Compaction was the main factor for the destruction of primary porosity along with cementation effect. The porosity in the limestone was significantly enhanced by late stage dissolution, fractures enclosed by calcite cement and dolomitization. Â© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.